Learning Strategies in Developing Character of Primary School Students in the Era of Revolution - Muthia Pasha Syah (International Journal of Students Education, 2024)
This article aims to explore elementary school teachers’ learning strategies in developing the character of elementary school students in the era of revolution. Character education is important, especially in facing a new era that is challenging and influential in all fields including the field of education. This research uses a qualitative approach with this type of study case, where the researcher conducted an in-depth exploration of the learning activities and processes carried out by elementary school teachers. The data collection instruments used were interview and observation guidelines. Next, data analysis used a descriptive method with three stages, namely data condensation, data display, and drawing conclusions or verification. The results of this research show several learning strategies that can support character development, including NHT [number heads together], playing strategies, role playing, singing, direct method, question and answer, scaffolding, modeling, and behavioral [reinforcement & punishment]. character. developed from these various strategies, including responsibility, independence, honesty, self-confidence, empathy and courage.